The challenge of the African “other”: formation of the identity and invention of Africa (s) based on Pepetela’s novel “the generation of utopia” - de Oliveira Neto, João Matias (ODEERE, 2016)
This article analises the construction of Africa based on the actual construction of the "other" as a challenge to the social sciences and humanities. From a reflection about the formation of Africa, many terms and nationalisms were used to dissert about what defines the African continent, and also what is Africa in different perspectives, regions and identity. From my study of the novel A Geração da Utopia, of angolan writer Pepetela, we discuss a process from which the difficulty in arriving at an understanding of identity can prove a greater challenge to us. First, understand how multiple identities are built as a inheritance of a nationalist perspective of identity. Second, how writers in their own way reflects about Africa within specific contexts. Keywords: identity, Angola, Pepetela, miscegenation, nationalism, history.